2020
DOI: 10.1111/ddi.13140
|View full text |Cite
|
Sign up to set email alerts
|

Multiple‐scale interactions structure macroinvertebrate assemblages associated with kelp understory algae

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 122 publications
(223 reference statements)
1
14
0
Order By: Relevance
“…More generally, our study has shown that light availability and sea temperature are critical factors influencing the structure of kelp populations in the U.K. Given that the habitats these kelp species underpin have considerable socioeconomic importance, for targeted finfish and crustaceans (Bertocci et al 2015), inshore food webs (Bué et al 2020), and carbon cycling (Pessarrodona et al 2018), improved understanding of the effects of environmental change is vital for their conservation and management. Any reductions in coastal water quality leading to increased turbidity and light attenuation will likely lead to declines in depth penetration, plant size and standing biomass, while also facilitating the spread and competitiveness of non‐native kelps (Epstein et al 2019 a , b ).…”
Section: Discussionmentioning
confidence: 92%
“…More generally, our study has shown that light availability and sea temperature are critical factors influencing the structure of kelp populations in the U.K. Given that the habitats these kelp species underpin have considerable socioeconomic importance, for targeted finfish and crustaceans (Bertocci et al 2015), inshore food webs (Bué et al 2020), and carbon cycling (Pessarrodona et al 2018), improved understanding of the effects of environmental change is vital for their conservation and management. Any reductions in coastal water quality leading to increased turbidity and light attenuation will likely lead to declines in depth penetration, plant size and standing biomass, while also facilitating the spread and competitiveness of non‐native kelps (Epstein et al 2019 a , b ).…”
Section: Discussionmentioning
confidence: 92%
“…In any case, at the local level, the ability to capture the benefits of positive ecosystem services and minimize adverse offsetting effects will depend on the local adaptive capacity, which is a multiscale phenomenon for a much more medium-long-term perspective, accounting for the economic resources, technology, information and skills, infrastructure, institutions, and equity in supporting processes of adaptation to climate change, with sensitivity drivers in the connection zones in which individuals, families, productive systems, and social structures and networks overlap [18,59,61]. Figure 9 shows a primary perspective on the complexity perspective developed in this article concerning the Boca de Cachón case.…”
Section: Discussion: Ecosystem Services and Local Interactions In A Rural Environmentmentioning
confidence: 99%
“…It implies a wide range-perspective and a complex dynamic interaction of positive and negative feedbacks between climate, social, ecological, economic, and cultural structures at different levels, such as individuals, households, communities, regions, and countries [15,16], allowing us to put the Boca de Cachón case in the analytical context of climate variability, and then supporting a context-specific local-based understanding of complexity as a multiscale interaction of environmental and climatic factors. It includes a dynamic of multilevel interaction between positive and negative ecosystem services synergies with local [17], national, and regional climatic patterns and the socio-economic factors that interact with the ecosystems and local climate variability at the local level [18]. Four epistemic elements are considered to expose the complex approach to the Boca de Cachón challenge as a study subject:…”
Section: Methodology: Building a Context-specific Approach To Complexitymentioning
confidence: 99%
“…Despite recent advances in the understanding of communities’ changes at different spatial scales (e.g. Bué et al., 2020; Leclerc, 2018; Robuchon et al., 2017), further exploration of beta‐diversity patterns and the underlying in situ environmental drivers is needed, particularly in highly dynamic ecosystems.…”
Section: Introductionmentioning
confidence: 99%
“…Studies focussing on temporal and spatial variations in the composition of communities (expressed as beta‐diversity) have shown an increasing homogenization (Dornelas et al., 2014; Magurran et al., 2015; Piazzi & Ceccherelli, 2020). Although coastal communities’ changes have been associated with the predicted warming (Bué et al., 2020), beta‐diversity is still poorly explored to understand climate change impacts on marine communities’ homogenization (Dornelas et al., 2014; Magurran et al., 2015; Piazzi & Ceccherelli, 2020). While recent studies have investigated the spatial scale dependency of biodiversity patterns and processes (Leclerc, 2018; Robuchon et al., 2017), temporal changes in beta‐diversity patterns remain overlooked.…”
Section: Introductionmentioning
confidence: 99%